Assessment of the Utilization of Digital Media for Reputation Management by a Leading Transportation Company (Company G), Abuja - Kwene, Ukpele Margaret; Tartsea-Anshase, Mercy (Lembaga Yasin AlSys, 2025)
This study investigates the use of digital media for online reputation management (ORM) by Company G, Abuja, with the aim of evaluating its strategies and impact on corporate image. A descriptive qualitative research design was employed, involving purposive sampling of 12 staff members across key departments responsible for reputation-related functions. Data were collected using a structured interview guide comprising 14 questions and analyzed thematically using the research questions as an analytical framework. Findings indicate that Company G actively utilizes a range of digital technologies to manage its reputation, with notable improvements observed over the past 3–4 years in areas such as brand visibility, complaint resolution, customer loyalty, sales conversion, and public trust. Despite these successes, the company continues to face challenges including negative reviews and misinformation. The study concludes that Company G has implemented a robust ORM strategy that effectively leverages digital tools to enhance corporate reputation. It recommends further investment in ORM, faster response times, stronger community engagement, the use of engagement incentives, and partnerships with influencer marketers to strengthen digital reputation management practices.